2016
DOI: 10.1063/1.4951715
|View full text |Cite
|
Sign up to set email alerts
|

Electron injection for direct acceleration to multi-GeV energy by a Gaussian laser field under the influence of axial magnetic field

Abstract: Electron injected in the path of a circularly polarized Gaussian laser beam under the influence of an external axial magnetic field is shown to be accelerated with a several GeV of energy in vacuum. A small angle of injection δ with 0∘<δ<20∘ for a sideway injection of electron about the axis of propagation of laser pulse is suggested for better trapping of electron in laser field and stronger betatron resonance under the influence of axial magnetic field. Such an optimized electron injection with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The optimum conditions for injection of high-energy electrons for the DLA are well discussed [11][12][13][14][15][16][17][18][19][20][21][22]. It has been noted that the energy gain obtained by electron depends on the phase of the laser field it has been injected into [19,21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The optimum conditions for injection of high-energy electrons for the DLA are well discussed [11][12][13][14][15][16][17][18][19][20][21][22]. It has been noted that the energy gain obtained by electron depends on the phase of the laser field it has been injected into [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Rigorous theoretical analyses for the specific DLA models have shown that the energy gain depends specifically on the relative phase of the laser radiation and the Eugen electron's oscillation in the plasma channel [11][12][13]. Besides of the injection phase, the optimal initial electrons' energies have been also analysed [12][13][14][15][16][18][19][20][21][22]. Role of the electron transverse energy in the * starodubtceva.em19@physics.msu.ru acceleration was demonstrated analytically [12] and the results [14,16,18,19] indicated that the optimal electron's injection condition corresponds to a quite large value of its transverse energy: p 0⊥ /mc ≈ (4 ÷ 6) (melectron mass, c -speed of light).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A resonance occurs between the electrons and the electric field of the laser if we apply an intense magnetic field in the direction of laser pulse propagation [12]. A small angle of injection for a sideway injection of electron about the axis of propagation of laser pulse is suggested for better trapping of electron in laser field and stronger betatron resonance under the influence of axial magnetic field [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%